AJIENG: DALAM ACARA KEMATIAN PADA MASYARAKAT HIANG, KABUPATEN KERINCI - Yolla Ramadani; Yelnim (Bajang Institute, 2022)
This article discusses the meaning of the symbol at the death of the Hiang community, Selihat Laut District, Kerinci Regency. In every death event, usually the community will provide as much assistance as possible to the bereaved family and not burden the bereaved family. However, for the Hiang community, the family left behind will spend a large amount of money to prepare Ajieng. Ajieng is given by the family who is left sincerely because it has a symbolic meaning. The symbols in the event of death were analyzed with the theory of symbolic interpretism by Clifford Geertz. The results of the study reveal that the meaning of the symbols in the death event is a tribute to the souls of the deceased so that the path to Allah SWT can be launched